2007
DOI: 10.1249/mss.0b013e318093f585
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Volume Response to 30-s Cycle Ergometry

Abstract: Our data show that short-duration, high-intensity cycle ergometer exercise tests can induce significant plasma volume decreases in untrained subjects, which may affect the interpretation of bloodborne biochemical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
5
8
0
Order By: Relevance
“…One limitation of our study is that possible changes in plasma volume concentration (PVC) through short‐time exercise were not taken into consideration. It has been shown that in high‐intensity, short‐time exercise with cycle ergometer changes of PVC of 12–15.6% can be found (van Beaumont et al, 1973; El‐Sayed et al, 1990; Gillen et al, 1991; Boulay et al, 1995; Kargotich et al, 1998) and biochemical data should be corrected for PVC (Kargotich et al, 1997; Retallick et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of our study is that possible changes in plasma volume concentration (PVC) through short‐time exercise were not taken into consideration. It has been shown that in high‐intensity, short‐time exercise with cycle ergometer changes of PVC of 12–15.6% can be found (van Beaumont et al, 1973; El‐Sayed et al, 1990; Gillen et al, 1991; Boulay et al, 1995; Kargotich et al, 1998) and biochemical data should be corrected for PVC (Kargotich et al, 1997; Retallick et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The average intra-assay coefficient of variation (calculated for ten duplicated samples) for MDA and CK was 7.5 and 8.3 %, respectively. Due to the decreased plasma volume following exercise [ 30 ], plasma volume was corrected for post-exercise changes by considering the changes in hematocrit according to the Dill and Costill method [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…This mechanism of muscle damage has been observed, for instance, among rugby players due to repetitive collisions [12]. The final CK level was, however, approximately three-fold lower than the average values recorded among male wrestlers during their preparatory and competition season [21], which resulted in the well-documented gender differences.…”
Section: Discussionmentioning
confidence: 76%
“…Short lasting, very intensive effort triggers a temporary and transient plasma volume (PV) decrease of 10-15% [10,21]. Thus, this effect contributes to the rise of each plasma parameter by a similar value regardless of the contribution to the other factors influencing the concentration, such as the rates of the secretion and elimination from circulation.…”
Section: Study Limitationsmentioning
confidence: 99%